2022
DOI: 10.1038/s41598-022-23345-z
|View full text |Cite
|
Sign up to set email alerts
|

Microdamage analysis of single-use flexible ureteroscope immediately after lithotripsy use

Abstract: This prospective ex vivo study investigated microdamage to single-use flexible ureteroscopes (fURS) after ureteroscopy and endoscopic combined intrarenal surgery (ECIRS). The performance of 30 WiScope devices (OTU Medical, San Jose, CA, USA) was examined immediately after use, dividing them into three equal groups: ureteroscopy and ECIRS in the prone and supine positions. The overall scope of microdamage assessment included the scope deflection, bending radius, resolution, and water flow rate. Additionally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…14,15 Thermal laser damage is known to occur most often in the distal 4 mm of the ureteroscope. 16,17 A recurrent theme from the reports was use of excess force by the surgeon, which resulted in instrument malfunction (eg over deflection) and/or serious injury (eg forceful removal of scope despite resistance, resulting in ureteral avulsion). Our results also serve as a reminder that while the surgeon does carry responsibility regarding their surgical technique, delivery of a safe URS service is truly a team effort.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Thermal laser damage is known to occur most often in the distal 4 mm of the ureteroscope. 16,17 A recurrent theme from the reports was use of excess force by the surgeon, which resulted in instrument malfunction (eg over deflection) and/or serious injury (eg forceful removal of scope despite resistance, resulting in ureteral avulsion). Our results also serve as a reminder that while the surgeon does carry responsibility regarding their surgical technique, delivery of a safe URS service is truly a team effort.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic combined intra‐renal surgery (ECIRS) is also argued as a scenario to consider SU models. However, a recent study found that use of accessories such as baskets rendered more damage to ureteroscopes than performing ECIRS 62 . It may be that with laser advancements such as pulse modulation and improved dusting capabilities, requirement for basket use goes down and scopes maintained longer.…”
Section: Arguments For Reusable Ureteroscopesmentioning
confidence: 99%